Exact and metaheuristic algorithms for the vehicle routing problem with a factory-in-a-box in multi-objective settings. (April 2022) - Pasha, Junayed; Nwodu, Arriana L.; Fathollahi-Fard, Amir M.; Tian, Guangdong; Li, Zhiwu; Wang, Hui; Dulebenets, Maxim A.
Highlights: A vehicle routing problem with a factory-in-a-box in multi-objective settings is studied. A multi-objective formulation is proposed to compromise the conflicting cost components. A novel customized nature-inspired evolutionary algorithm is developed to solve the problem. Numerical experiments are performed considering well-known exact and metaheuristic methods. A detailed analysis of solutions is conducted to draw managerial insights. Abstract: Emergencies, such as pandemics (e.g., COVID-19), warrant urgent production and distribution of goods under disrupted supply chain conditions. An innovative logistics solution to meet the urgent demand during emergencies could be the factory-in-a-box manufacturing concept. The factory-in-a-box manufacturing concept deploys vehicles to transport containers that are used to install production modules (i.e., factories). The vehicles travel to customer locations and perform on-site production. Factory-in-a-box supply chain optimization is associated with a wide array of decisions. This study focuses on selection of vehicles for factory-in-a-box manufacturing and decisions regarding the optimal routes within the supply chain consisting of a depot, suppliers, manufacturers, and customers. Moreover, in order to contrast the options of factory-in-a-box manufacturing with those of conventional manufacturing, the location of the final production is determined for each customer (i.e., factory-in-a-box manufacturing with production at the customer location or conventional manufacturing with production at the manufacturer locations). A novel multi-objective optimization model is presented for the vehicle routing problem with a factory-in-a-box that aims to minimize the total cost associated with traversing the edges of the network and the total cost associated with visiting the nodes of the network. A customized multi-objective hybrid metaheuristic solution algorithm that directly considers problem-specific properties is designed as a solution approach. A case study is performed for a vaccination project involving factory-in-a-box manufacturing along with conventional manufacturing. The case study reveals that the developed solution method outperforms the ε-constraint method, which is a classical exact optimization method for multi-objective optimization problems, and several well-known metaheuristics.